2014
DOI: 10.4028/www.scientific.net/amr.996.307
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Influence Factors on Residual Stress Determination within Coated Surfaces in Consideration of the Differential and Integral Method

Abstract: Abstract. To improve the surface behavior of metal structures, like wear-and heat resistance or hardness, often thermally sprayed ceramic coatings are applied. A modern technology to realize dense layers is the High Velocity Oxygen Fuel (HVOF) technique. The deposition process and necessary pretreatments can cause high residual stresses within the coating and the substrate. While tensile stresses in the brittle coating may cause cracks, compressive stress states can even improve the materials behavior. To guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In order to determine these stresses it is possible to drill a hole into the component and measure the occurring deformations with strain gauges. These strains can then be recalculated to get the governing depth dependent residual stress [2]. This procedure is called incremental hole drilling and the cut-out is usually imposed stepwise by a mechanical drill.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine these stresses it is possible to drill a hole into the component and measure the occurring deformations with strain gauges. These strains can then be recalculated to get the governing depth dependent residual stress [2]. This procedure is called incremental hole drilling and the cut-out is usually imposed stepwise by a mechanical drill.…”
Section: Introductionmentioning
confidence: 99%
“…1). For this determination a mechanical IHD operation was conducted, where an integral method (IM) evaluation scheme with a case sensitive calibration was applied [1]. Further numerical studies showed, that the high values after 200 µm depth might be mainly related to a plastification process due to the stress intensification around the hole.…”
Section: Boundary Conditions and Set-upmentioning
confidence: 99%